2022
DOI: 10.3390/biomedicines10102460
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Peritoneal Fluid ZEB Levels in Patients with Endometriosis and Infertility

Abstract: Zinc finger E-box-binding homeobox 1 (ZEB1) and zinc finger E-box-binding homeobox 2 (ZEB2) are transcription factors that regulate epithelial–mesenchymal transformation (EMT). The aim of this study was to compare levels of ZEB1 and ZEB2 in the peritoneal fluid and plasma between patients with and without endometriosis in order to assess their utility in the diagnostic process. Plasma and peritoneal fluid samples were collected from 50 patients with and 48 without endometriosis during planned surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Similarly, dysregulations in the epithelial−mesenchymal transformation may contribute to the development of this disease. 4246 Properly functioning mesothelial barrier prevents stromal cells from endometrial cells invasion and the formation of extrauterine endometrial lesions. 43 It was reported in genome-wide association studies that endometriosis is linked with changes in expression of genes ( WNT4 , CDC42 , ID4 , VEZT ) actively participating in the regulation of cytoskeleton and mesothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, dysregulations in the epithelial−mesenchymal transformation may contribute to the development of this disease. 4246 Properly functioning mesothelial barrier prevents stromal cells from endometrial cells invasion and the formation of extrauterine endometrial lesions. 43 It was reported in genome-wide association studies that endometriosis is linked with changes in expression of genes ( WNT4 , CDC42 , ID4 , VEZT ) actively participating in the regulation of cytoskeleton and mesothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Furuya et al 44 reported the expression of ZEB1 in the epithelial cells of endometriotic lesions with its absence in the eutopic endometrial tissue, which might suggest ZEB1 as a potential indicator of endometriosis invasiveness. In a study by Bartnik et al, 46 the authors observed significant differences in ZEB2 plasma levels between patients with and without infertility.…”
Section: Epithelial-mesenchymal Transformationmentioning
confidence: 93%
“…On the other hand, the association of other Zn-requiring molecules, ZEB1 and ZEB2, which are indisputably involved in the EMT process [ 86 , 87 ], with endometriosis is much less well investigated. While some researchers have noticed a positive association between ZEB1 and ectopic endometrial lesions [ 96 ], others have not observed any relationships [ 97 ]. Additionally, we found no reports suggesting that Zn deficiency may impair ZEB1 and ZEB2 expression.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%
“…Other theories emphasize the involvement of genetic, environmental, and immunological factors in predisposing the development of the disease (3). Disturbed immunoregulatory mechanisms, accompanied by various inflammatory markers such as immune cells, cytokines, chemokines, metalloproteinases, cathepsin, and other immunologically-related substances, have been implicated in the development, invasion, and angiogenesis of ectopic lesions (11)(12)(13)(14)(15)(16)(17)(18). However, none of these theories fully explain the complexity underlying the pathogenesis of endometriosis.…”
Section: Introductionmentioning
confidence: 99%